2008
DOI: 10.1107/s0108768108037361
|View full text |Cite
|
Sign up to set email alerts
|

Structural study of K x Na1 − x NbO3 (KNN) for compositions in the range x = 0.24–0.36

Abstract: The structure of the A-site substituted perovskite K(x)Na(1 - x)NbO(3), x = 0.24-0.36, where a phase boundary was previously reported, has been determined by high-resolution X-ray powder and neutron powder diffraction studies. The structure of the x = 0.3 compound was refined in the monoclinic space group Pm at 293 K and in P4mm at 523 K. The Glazer tilt system of the room-temperature monoclinic phase is a(0)b(+)c(0), which has implications for the nature of the next symmetry change with composition towards pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 16 publications
1
32
1
1
Order By: Relevance
“…[14][15][16] The phase diagram for solid solutions of K x Na 1Àx NbO 3 has been extensively studied. [17][18][19][20][21][22][23][24] The sequence of phase transitions of the KNbO 3 end-member on cooling is cubic (C, Pm 3m) À! $420 C tetragonal (T, P4mm) À!…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] The phase diagram for solid solutions of K x Na 1Àx NbO 3 has been extensively studied. [17][18][19][20][21][22][23][24] The sequence of phase transitions of the KNbO 3 end-member on cooling is cubic (C, Pm 3m) À! $420 C tetragonal (T, P4mm) À!…”
Section: Introductionmentioning
confidence: 99%
“…40 They occur in the compositionally induced low-symmetry intermediate structures as a result of the frustrated competition between displacive variants with different polarization vectors. 41 In K 0.26 Na 0.74 NbO 3 at room temperature, Baker et al 37 showed a 1/2(323) superlattice peak (where h ¼ l) in the X-ray diffraction data and described the Pm monoclinic phase with both a 0 b þ c 0 tilting and cation displacements order. Therefore, the appearance of the 1/2{oeo} diffraction spots in both [111] and [110] zone axes at 14 kV/cm in KNN-5.2LS is due to an electric field-induced phase transition from the orthorhombic Amm2 phase, which has no oxygen octahedra tilting, to the monoclinic Pm phase with a 0 b þ c 0 tilting, combined with antiparallel cation displacements.…”
Section: B Ex Situ X-ray Diffraction Measurementsmentioning
confidence: 99%
“…36,37 They originated from the a 0 b þ c 0 oxygen octahedra tilting in the monoclinic space group Pm. At 25 C, this monoclinic phase is stable in the composition range of 0.25 < x < 0.40.…”
Section: B Ex Situ X-ray Diffraction Measurementsmentioning
confidence: 99%
“…A combination of a theoretical and experimental approach to investigate the properties of KNN at x ¼ 0.5 has been reported where it was stated that a rhombohedral phase exists at room temperature which could not be detected earlier using X-ray diffraction [11]. A detailed structural study of (K x Na 1Àx )NbO 3 has also been carried out where x ranges from 0.24 to 0.36 and the results presented varied slightly from previous reports with a phase coexistence region at the transition between monoclinic and tetragonal phases [12]. Evidence was also found to support the earlier assertion that intermediate oxygen octahedral tilting is present in the tetragonal phase.…”
Section: Introductionmentioning
confidence: 69%